Exhausting modernity : grounds for a new economy - Brennan, Teresa, 1952-2003 (Routledge, 2000)
Exhausting Modernity is a bold, exciting new work on the exhaustion of our resources, both natural and human. Brennan marshalls the insights of Marx and Freud to provide a compelling and insightful analysis of the pervading modern capitalism: environmental collapse, rising poverty levels, and the increased global economic disparity. Linking the consumption of environmental resources to our own depleted psychic life, she argues that modernity must be rethought if we are to find a sustainable future for both the environment and our own psychic life.